Life Expectancy of Transplanted Livers - HOPE Against Aging? - Eden, Janina; Müller, Philip C; Kuemmerli, Christoph; Aegerter, Noa; Brüggenwirth, Isabel Ma; Berlakovich, Gabriela; Buchholz, Bettina M; Botea, Florin; Camagni, Stefania; Cescon, Matteo; Cillo, Umberto; Colli, Fabio; et al. (Annals of surgery, 2025)
OBJECTIVE: To investigate the impact of cumulative liver age on graft survival in liver transplant recipients. SUMMARY OF BACKGROUND DATA: Organ shortage has led to increased use of elderly donor livers for an ageing group of recipients, particularly in Europe. We hypothesized that hypothermic oxygenated perfusion (HOPE) enhances graft resilience against aging in livers from elderly donors. METHODS: This post-hoc analysis of the multicenter European HOPE-REAL study (NCT05520320) examined liver age in adult recipients of HOPE-treated brain-dead donor (DBD) livers. Cumulative liver age was defined as the sum of donor age and post-transplant graft survival. HOPE-treated DBD liver transplants were compared with a single-center control cohort of non-perfused DBD livers using propensity score matching to adjust for confounders. RESULTS: The median cumulative liver age was significantly higher in the HOPE-treated (n=768) cohort than in the non-perfused (n=863) group (69 vs. 61 years, P<0.001), yet graft survival was superior in the HOPE-treated group (log-rank P<0.001). After matching, cumulative liver age remained significantly higher in the HOPE group (P<0.001). Multivariate analysis identified HOPE as an independent predictor of cumulative liver age (P<0.001). CONCLUSIONS: HOPE treatment appears to mitigate the risks associated with transplanting elderly DBD livers, leading to excellent long-term survival in an ageing recipient population. These findings support broader adoption of HOPE to improve utilization of older donor livers and expand the donor pool.
Keywords: machine liver perfusion; cumulative liver age; liver transplantation